2014
DOI: 10.1016/j.drugpo.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of methamphetamine (“tik”) on a peri-urban community in Cape Town, South Africa

Abstract: Background Over the last decade, South Africa’s Western Cape has experienced a dramatic increase in methamphetamine (“tik”) use. Our study explored local impressions of the impact of tik use in a peri-urban township community in Cape Town, South Africa. Methods We conducted individual in-depth interviews with 55 women and 37 men who were regular attendees of alcohol-serving venues. Interviews were recorded and transcribed. A content analysis approach was used to identify themes related to the impact of tik u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…Respondents often noted desperation for getting the drug, and the setting of high poverty and unemployment meant that people often had to turn to illicit or informal means to procure drugs. While men often participate in petty or violent crime to support their drug habit (Watt et al, 2014), women did not appear to have this option. This disparity in access to resources made sex a tradable resource, and sex trading appeared to be a way that women could share in men's spoils from criminal activity and gain access to drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents often noted desperation for getting the drug, and the setting of high poverty and unemployment meant that people often had to turn to illicit or informal means to procure drugs. While men often participate in petty or violent crime to support their drug habit (Watt et al, 2014), women did not appear to have this option. This disparity in access to resources made sex a tradable resource, and sex trading appeared to be a way that women could share in men's spoils from criminal activity and gain access to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Only about 27% of residents of Delft have completed a high school education or more, and very few have steady employment (Statistics South Africa, 2012). Previous research in Delft has suggested that tik use is highly prevalent with far-reaching impacts on the community (Watt et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…In South Africa, methamphetamine use is described as 'ubiquitous' in some communities and its impact can be quantified on an individual, interpersonal and community basis [37]. Its use among different populations poses different threats to the individual's and community's health and wellbeing, depending on the infrastructure, economic, and social reserve of that population.…”
Section: Methamphetamine In Special Risk Groupsmentioning
confidence: 99%
“…These women were also at increased risk for sexually transmitted infection than nonmethamphetamine users. Uniformly, they cited methamphetamine as the 'power drug' that increases their functioning capacity and enabling them to work longer hours and see more clients [13,37,40]. When methamphetamine was used in conjunction with other injected drugs, it was associated with risky injection practices such as needlesharing, hurried injection, and reuse of injection equipment leading to increased HIV seroconversion [22,38,41,42].…”
Section: Methamphetamine and Increased Sexual Health Risksmentioning
confidence: 99%
“…In South Africa, methamphetamine users living in peri-urban township communities are a population that could benefit from STTR efforts. In this setting, methamphetamine users are a hard-to-reach group due to the illegal nature of the behavior and a strong stigma against users [7]. To date, there is very little data on HIV testing behaviors, attitudes towards testing, and HIV prevalence in this population.…”
Section: Introductionmentioning
confidence: 99%